Factors that Influence the Financial Performance of Conventional Banks - Sam, Toong Hai; Machmuddah, Zaky; Safitri, Ayu; Rohman, Abdul; Feng, Li; Hong, Zhu Yuan (Journal of Ecohumanism, 2025)
In 2023, banking performance in Indonesia will slow down. This can cause potential investors and investors to reduce their interest in investing in banking in Indonesia. The purpose of this study is to prove the factors that influence the financial performance of conventional banking in Indonesia. Data analysis using WarpPLS, with a sample of 235 observation data. The data was obtained from the predetermined sample selection process. This study has succeeded in proving that the financial performance of conventional banking is influenced by Operating Costs to Operating Revenue (OCOR) and Loan to Deposit Ratio (LDR). While the Capital Adequacy Ratio (CAR) does not affect it. The implication of this research is the importance of the role of regulators in regulating banking policies in Indonesia in terms of development governance, considering the opportunities and challenges of the increasingly complex business world today.